What are the key drivers to promote entrepreneurial intention of vocational college students? An empirical study based on structural equation modeling - Niu, Xinchen; Niu, Zhining; Wang, Mengmeng; Wu, Xueshi (Frontiers in Psychology, 2022)
In order to alleviate the increasing employment pressure of vocational college students, the current study is an attempt to explore the factors of entrepreneurial intention affecting vocational college students. The study investigates whether entrepreneurial self-efficacy and attitude mediate this relationship between creativity and entrepreneurial intentions. In particular, this research also examines whether risk propensity moderates the relationship. An empirical survey was conducted and a total of 500 valid questionnaires were collected through online platforms. The data is analyzed by employing Partial Least Squares Structural Equation Modeling. The results indicate that self-efficacy is the strongest antecedent of entrepreneurial intention. Social support is found to influence entrepreneurial intention significantly, while the direct effect of creativity on intention is very marginal. Moreover, the results of the mediation analysis show that the relationship between creativity and entrepreneurial intention is fully mediated by self-efficacy and attitude, while the effect of social support on entrepreneurial intention is partially mediated. Specifically, the moderation effect of risk propensity on the relationship between creativity and entrepreneurial intention is acknowledged. Concrete suggestions are proposed for vocational colleges and governments to promote students’ entrepreneurial intentions. Finally, implications for the findings are provided.